Undocumented politics : place, gender, and the pathways of Mexican migrants - Andrews, Abigail (University of California Press, 2018)
"Undocumented politics is a poignant ethnography of gender and political agency in North America's most excluded migrant communities. Author Abigail Andrews takes us from the Indigenous villages of Oaxaca, Mexico into the lives of undocumented families in the barrios of Southern California and back. Drawing on two years of transnational fieldwork, archives, surveys, and the voices of migrants themselves, she compares the histories of two very distinct transnational communities. The book reveals how migrants' cross-border struggles are shaped by local practices of control, in both the places they live and the places they leave behind"--Provided by publisher.